Advances in the management of severe aortic stenosis. (May 2016) - O'Sullivan, K.; Bargenda, S.; Sugrue, D.; Hurley, J.
Abstract Background Recent developments in the management of severe aortic stenosis have resulted in a paradigm shift in the way we view the condition. Patients previously denied intervention in the form of surgical aortic valve replacement (SAVR) are now candidates for transcatheter aortic valve implantation and the risk and age profiles of those undergoing SAVR are rising with the ageing population. This review article is designed to provide an overview of developments in the surgical management of severe aortic stenosis. We also discuss the expanding role of minimally invasive surgical approaches to outline the current techniques available to treat patients with severe aortic stenosis. Methods PubMed was searched using the terms 'severe aortic stenosis', 'surgical aortic valve replacement', 'transcatheter aortic valve replacement', 'mechanical aortic valve replacement' and 'sutureless aortic valve replacement'. Selection of articles was based on peer review, journal and relevance. Where possible articles from high-impact factor peer review journals were included. Results Minimally invasive operative approaches include mini-sternotomy and mini-thoracotomy. Sutureless aortic prostheses reduce aortic cross-clamp time and cardiopulmonary bypass time; however, long-term follow-up data are unavailable at this time. Mechanical prostheses are advised for those under 60. Conclusion Multiple advances in the surgical management of aortic stenosis have occured in the past decade. An evolving spectrum of surgical and transcatheter interventions is now available depending on patient age and operative risk.